2021
DOI: 10.7759/cureus.15816
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Misuse: An Epidemic Within a Pandemic

Abstract: Coronavirus disease 2019 (COVID-19) had deleterious effects on patients with mental health problems and several studies have shown a spike in the rates of depression, insomnia, and post-traumatic stress disorder. Anxiety and insomnia rates have also increased among both the general public and health care professionals. Benzodiazepines are some of the most commonly used drugs in the treatment of anxiety and insomnia. However, benzodiazepines are also misused, abused alone, or abused in combination with other dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 38 publications
0
44
0
1
Order By: Relevance
“…They are involved in the antihyperalgesic effect of the GABAA receptor that is a target for benzodiazepines in the spinal cord, along with which the GABAA receptors have been seen to play a role in the regulation of mood and antidepressant therapy [ 11 ]. Along with treating chronic pain-induced depression, benzodiazepines are also used for treating anxiety and insomnia, both of which can be seen in chronic pain patients [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They are involved in the antihyperalgesic effect of the GABAA receptor that is a target for benzodiazepines in the spinal cord, along with which the GABAA receptors have been seen to play a role in the regulation of mood and antidepressant therapy [ 11 ]. Along with treating chronic pain-induced depression, benzodiazepines are also used for treating anxiety and insomnia, both of which can be seen in chronic pain patients [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Due to increased prescription of the drugs, misuse has become more prevalent, especially in the recent coronavirus disease 2019 (COVID-19) pandemic, which led to increased social distancing, isolation, and loneliness, all of which contribute to depression, anxiety, or insomnia [ 30 ]. The motivations for misusers have been to help with sleep, experimentation, and to get "high" [ 30 ]. The methods for obtaining benzodiazepines have been primarily from family or friends compared to doctors [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of extended-release venlafaxine, the response rate was 78% and the remission rate was 40% in patients with PTSD [ 31 ]. In addition to SSRIs and SNRIs, benzodiazepines (BZDs) have been utilized for patients with PTSD [ 32 ]. However, due to their anxiolytic, sedative, hypnotic, and skeletal muscle-relaxing effects, BZDs have become widely abused amongst this population [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition to SSRIs and SNRIs, benzodiazepines (BZDs) have been utilized for patients with PTSD [ 32 ]. However, due to their anxiolytic, sedative, hypnotic, and skeletal muscle-relaxing effects, BZDs have become widely abused amongst this population [ 32 ]. Studies have found that this trend of misuse has only increased with the recent COVID-19 global pandemic [ 32 ].…”
Section: Reviewmentioning
confidence: 99%